Lycium barbarum polysaccharide inhibits retinal neovascularization and inflammation in vitro and in vivo - Bin Wu; Xue Wang; Wei Zhang; Xin Wang; Qi-Miao Wang; Ya-Ju Pang; Yi-Chun Kong (International Journal of Ophthalmology)
AIM: To explore the effect and mechanism of Lycium barbarum polysaccharide (LBP) inhibiting retinal neovascularization. METHODS: In vitro tests were performed on human retinal microvascular endothelial cells (HRECs) from three groups, including control group (normal oxygen), hypoxic group (hypoxia at 37℃, 1% O2, 5% CO2, and 94% N2), and LBP group (hypoxic group with LBP 100 μg/mL). In vivo experiments, C57 mice were divided into three groups: control group (normal rearing group), the oxygen-induced ischemic retinopathy (OIR) group, and the OIR with 50 mg/kg LBP group. Retinal neovascularization was observed by fluorescein angiography and quantified. Retinal thickness was evaluated by Hematoxylin and eosin (HE) stain. The expression of epidermal growth factor receptor (EGFR), phosphatidylinositol 3-kinase (PI3K), mammalian target of rapamycin (mTOR), phosphorylated mammalian target of rapamycin (p-mTOR), protein kinase B (AKT), phosphorylated protein kinase B (p-AKT), interleukin-1β (IL-1β), inducible nitric oxide synthase (iNOS), and tumor necrosis factor-α (TNF-α) in each group were analyzed by Western blot. IL-1β level in retina was analyzed using immunohistochemical staining. RESULTS: The increased area of neovascular clusters in OIR mice was significantly decreased by LBP. Retinal thickness of OIR mice was significantly thinner compared with normal oxygenated mice and was increased in LBP group. Compared with those in the hypoxic groups, Western blotting of HRECs and retinal tissues revealed that the expression of EGFR, PI3K, p-mTOR, p-AKT, IL-1β, iNOS, and TNF-α decreased in the LBP group but was still greater than that in control group. Moreover, IL-1β was reduced in retinal sections treated with LBP. In the scratch test, the cell migration of the hypoxic group was significantly greater than that of the control group, while LBP treatment attenuated this increase in migration. CONCLUSION: LBP reduces retinal neovascularization and inflammation in vivo and inhibits the migration of HRECs in vitro by regulating the EGFR/PI3K/Akt/mTOR signaling pathway.